Ultrabroadband Photodetectors up to 10.6 µm Based on 2D Fe3O4 Nanosheets. Issue 25 (13th May 2020) - Yin, Chujun; Gong, Chuanhui; Chu, Junwei; Wang, Xudong; Yan, Chaoyi; Qian, Shifeng; Wang, Yang; Rao, Gaofeng; Wang, Hongbo; Liu, Yuqing; Wang, Xianfu; Wang, Jianlu; et al.
Abstract: The ultrabroadband spectrum detection from ultraviolet (UV) to long‐wavelength infrared (LWIR) is promising for diversified optoelectronic applications of imaging, sensing, and communication. However, the current LWIR‐detecting devices suffer from low photoresponsivity, high cost, and cryogenic environment. Herein, a high‐performance ultrabroadband photodetector is demonstrated with detecting range from UV to LWIR based on air‐stable nonlayered ultrathin Fe3 O4 nanosheets synthesized via a space‐confined chemical vapor deposition (CVD) method. Ultrahigh photoresponsivity ( R ) of 561.2 A W −1, external quantum efficiency (EQE) of 6.6 × 10 3 %, and detectivity ( D *) of 7.42 × 10 8 Jones are achieved at the wavelength of 10.6 µm. The multimechanism synergistic effect of photoconductive effect and bolometric effect demonstrates the high sensitivity for light with any light intensities. The outstanding device performance and complementary mixing photoresponse mechanisms open up new potential applications of nonlayered 2D materials for future infrared optoelectronic devices. Abstract : Novel nonlayered 2D Fe3 O4 nanosheets with cubic inverse‐spinel structure deliver an ultrabroadband photoresponse from the ultraviolet to the long‐wavelength infrared (LWIR) range. The distinguished LWIR detection performance with ultrahigh photoresponsivity of 561.2 A W −1, external quantum efficiency of 6.6 × 10 3 %, and detectivity of 7.42 × 10 8 Jones can be attributed to a synergistic effect of the photoconductive effect and the bolometric effect.